Possible approaches to reproduction of endothelial dysfunction. searching for the optimal model - I. B. Tsorin; L. V. Kozhevnikova; S. A. Simonenko; I. F. Sukhanova; M. B. Vititnova; S. A. Kryzhanovskii (LLC "Publisher OKI", 2024)
Purpose of the study. Search for an optimal approach to developing a translational model of endothelial dysfunction (ED).Materials and methods. The experiments were carried out on 58 white male rats, which were randomized into 8 groups: 1st (n = 6) - control for L-methionine (in vitro experiments); 2nd (n = 6) - L-methionine (in vitro experiments); 3rd (n = 6) - control for L-NAME (in vitro experiments); 4th (n = 6) - L-NAME (in vitro experiments); 5th (n = 10) - control for L-methionine (in vivo experiments); 6th (n = 7) - L-methionine (in vivo experiments); 7-a (n = 10) - control for L-NAME (in vivo experiments); 8th (n = 7) - L-NAME (in vivo experiments). In groups 2 and 6, animals were intragastrically administered L-methionine (3 g/kg/day for 7 days), and rats in groups 4 and 8 were administered i.p. with L-NAME (0.025 g/kg/day within 7 days). Control animals received an equivalent volume of solvent. In in vitro experiments, a four-channel myograph (Danish Myo Technology) was used to record the tonic activity of the aortic rings. The contraction strength of the aortic rings caused by norepinephrine (10−7 M) and carbachol (10−5 M) was recorded in isometric mode. In in vivo experiments on anesthetized rats (urethane 1300 mg/kg i.p.), blood microcirculation in the myocardium and skeletal muscle was recorded using laser Doppler flowmetry using a computerized laser analyzer "LAZMA-D" (manufactured by NPP "Lazma", Russia). When assessing microblood flow, the perfusion index (M) was calculated in perfusion units (perf.u.).Results. In vitro experiments have shown that under conditions of hyperhomocysteinemia caused by L-methionine, the vascular response to norepinephrine remains practically unchanged. At the same time, the vasodilating response to carbachol (10−5 M) statistically significantly decreased by 57 % (p = 0.005). In animals treated with L-NAME, not only did the response to carbochol decrease by 55 % (p = 0.009), but also the vasoconstrictor response to norepinephrine increased by 48 % (p = 0.003). Under conditions of ED caused by both hyperhomocysteinemia and L-NAME, blood microcirculation in the myocardium and skeletal muscle is significantly reduced. It has also been shown that in the conditions of the L-NAME-induced ED model, in contrast to the L-methionine-induced ED model, there is no drop in rat body weight and practically no mortality.Conclusion. Thus, ED induced by both hyperhomocysteinemia and L-NAME blockade of endothelial nitric oxide synthase is accompanied by similar changes in blood microcirculation in the myocardium and skeletal muscle. However, taking into account the results of in vitro experiments, we can conclude that the model of ED induced by L-NAME seems more promising, under which, in contrast to ED induced by L-methionine, the vasodilatory response of the vessel to carbachol is not only suppressed, but also the vasoconstrictor reaction to norepinephrine is activated.